GAMBARAN PROBLEMATIKA KOMUNIKASI RUMAH TANGGA KRISTEN DI KOTA KUPANG - Mieke Yen Manu; Yanti Secilia Giri; Yudhi Kawangung (POIMEN Jurnal Pastoral Konseling, 2020)
Marriage will occur if each partner feels they are compatible, complementary, respectful, able to receive. However, marriage is not as smooth as they imagined when they were not married because there will be a variety of new problems that must be faced. The reason for this research is that poor communication can cause many problems in a Christian family. Communication plays a very important role in married life. As for the formulation of the problem that this research wants to answer, How big is the picture of communication problems in Christian households in the city of Kupang? What type of communication is used? How much does the church carry out Christian household accompaniment? This study surveyed 116 respondents who were married in the city of Kupang using Simple Random Sampling techniques. The instrument used was a questionnaire based on the Gultman scale with two answer choices. Based on the results of the study concluded that the description of communication problems in Christian households in the city of Kupang is in the near-low category at 33.10%. The type of non-verbal communication used by research respondents was 68.10%. Based on 52.17% of respondents answered that the church does not carry out the task of assisting Christian household communication problems.